Oligarchy and Orature in the Novels of Nuruddin Farah - Derek Wright (Studies in 20th & 21st Century Literature, 1991)
In Farah's fiction Somali oral traditions are shown to possess a resilient strength and even a revolutionary vitality. Yet they are not envisaged polemically, as unsullied alternatives and sources of counter-discourse to post-colonial realities: rather, they are shown to be implicated in their evils and corruptions. Faced with a mode of reality built on oral discourse, where the written word is ruthlessly suppressed, written texts either retreat into secret cipher or are themselves infiltrated by the vaporous oral reality of public life and take on selected elements of oral literary conventions: notably, their fluid indeterminacy of meaning and interpretative openness, their reinventive capacities and vagaries of characterization, and the uncentredness of audience-oriented modes of discourse. Modern Somalia and the lives of its dissident intellectuals are portrayed as correspondingly uncentred entities whose meanings are not traceable to any single stable order of reality but float in a multiplicity of versions. The narrative plot of Loyaan's quest for the truth of his brother's death in Sweet and Sour Milk is finally unable to unravel the political-criminal plot to murder and mythologize Soyaan, which dissolves amid a welter of conflicting oral testimony and runs out, unresolved, in loose ends.
Keywords: Farah; fiction; Somali; oral tradition; polemically; counter-discourse; post-colonial; oral discourse; written texts; written word; oral reality; oral; audience-oriented; Modern Somalia; narrative plot; narrative; Loyaan; brother' s death; brother; death; Sweet and Sour Milk; political; criminal; murder; mythologize; Soyaan; oral testimony; Nuruddin Farah; Oligarchy; Orature; Novel